2018
DOI: 10.1093/mnras/sty2951
|View full text |Cite
|
Sign up to set email alerts
|

SNR-calibrated Type Ia supernova models

Abstract: Current Type Ia supernova (SN Ia) models can reproduce most visible+IR+UV observations. In the X-ray band, the determination of elemental abundance ratios in supernova remnants (SNRs) through their spectra has reached enough precision to constrain SN Ia models. Martínez-Rodríguez et al have shown that the Ca/S mass ratio in SNRs cannot be reproduced with the standard nuclear reaction rates for a wide variety of SN Ia models, and suggested that the 12 C+ 16 O reaction rate could be overestimated by a factor as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 95 publications
6
65
1
Order By: Relevance
“…The filled gray area and yellow area show the observed values for W49B and 3C 397, respectively. The filled circles show the 1D models in Bravo et al (2019). The filled and hollow stars show the 2D (Maeda et al 2010) and 3D (Seitenzahl et al 2013) models, respectively. super-solar metallicity, such as Z = 8 +10 −4 Z , the Ni/Fe mass ratio in the NSE and n-NSE should be much higher than a few percent.…”
Section: W49b and Nickelmentioning
confidence: 99%
“…The filled gray area and yellow area show the observed values for W49B and 3C 397, respectively. The filled circles show the 1D models in Bravo et al (2019). The filled and hollow stars show the 2D (Maeda et al 2010) and 3D (Seitenzahl et al 2013) models, respectively. super-solar metallicity, such as Z = 8 +10 −4 Z , the Ni/Fe mass ratio in the NSE and n-NSE should be much higher than a few percent.…”
Section: W49b and Nickelmentioning
confidence: 99%
“…As references, I have selected two explosion models suitable for normal-luminosity SNIa, characterized by an ejected mass of 56 Ni about M( 56 Ni) ∼ 0.5 − 0.7 M . The first model, sub-M Ch , is a central detonation of a sub-Chandrasekhar WD of mass M WD = 1.06 M (model 1p06 Z9e-3 std in Bravo et al 2019). The second one, M Ch , is a delayed detonation of a massive WD with central density ρ c = 3 × 10 9 g cm −3 and a deflagration-to-detonation transition density ρ DDT = 2.4 × 10 7 g cm −3 (model ddt2p4 Z9e-3 std in Bravo et al 2019).…”
Section: Methodsmentioning
confidence: 99%
“…One example of this kind of tables of NSE properties is given in Seitenzahl et al (2009). Recently, Bravo et al (2019) reported that the final yields computed using their NSE table might disagree by order of magnitude for some isotopes with respect to those obtained computing the NSE state properties on the fly in the hydrodynamical calculation. The discrepancy did not affect significantly either the total energy release, that is the final kinetic energy, or the ejected mass of 56 Ni, and was attributed to the interpolation procedure applied to obtain the NSE properties out of the ρ, T , and Y e table nodes.…”
Section: Nuclear Statistical Equilibriummentioning
confidence: 99%
“…1-3 show the evolution of key quantities related to the branching of explosive oxygen burning into either the α-rich or the α-poor tracks. Specifically, the plots show the evolution of a mass shell reaching a peak temperature of 4 × 10 9 K in models 1p06_Z2p25e-4_ξ CO 0p9 and 1p06_Z2p25e-2_ξ CO 0p9, described in Bravo et al (2019). In short, both models simulate the detonation of a WD with mass 1.06 M made of carbon and oxygen, whose progenitor metallicities are respectively Z = 2.25 × 10 −4 (strongly sub-solar metallicity, hereafter the low-Z case) and Z = 0.0225 (about 1.6 times solar, hereafter the high-Z case).…”
Section: O(pα) 13 N and Metallicitymentioning
confidence: 99%
“…with f 0 = 0. The code used is the same as in Bravo et al (2019), where it is described in detail. The thermonuclear reaction rates used in the simulations are those recommended by the JINA REACLIB compilation (Cyburt et al 2010, hereafter REACLIB).…”
Section: O(pα) 13 N and Metallicitymentioning
confidence: 99%